Nurses’ knowledge about, and practices associated with, congenital syphilis in Basic Health Units (BHU) in Redenção County, Pará State, Brazil (Brazilian Journal of Health Research, 2021)
Introduction: Syphilis is a sexually transmitted infection caused by the highly contagious bacterial species Treponema pallidum, which is transmitted through unprotected sexual activity, as well as vertically transmitted during pregnancy. Objective: Evaluating the knowledge of nurses working in Basic Health Units (BHU) about congenital syphilis (CS). Methods: Quantitative cross-sectional study conducted with 8 nurses from Redenção County, Pará State, Brazil. Structured questionnaire on CS was applied to feature the professional profile of each nurse and their knowledge about clinical practice, diagnosis, treatment, epidemiological profile and notification of the investigated disease. Univariate statistical analysis was performed based on frequency distribution. Results: In total, 87.5% of participants were women. Most of them had access to the technical manual by the Ministry of Health and 50% of these nurses had adequate knowledge about the epidemiological status of CS at local and national level. In addition, 62.5% of the investigated professionals knew the way the disease was transmitted based on its stage, although this number has decreased when gestational age was taken into consideration. More than 50% of participants described the correct time when serological tests should be performed during pregnancy, but they did not have adequate knowledge about the classification of treponemal and non-treponemal tests. Conclusion: BHU nurses did not have adequate knowledge about the investigated topic and need better scientific basis to perform such actions. Thus, it is necessary providing technical training to these professionals in order to improve their performance, mainly at the time to treat pregnant women with syphilis.